Self-selection and the performance of return migrants: The case of Albania - Augustin de Coulon; Matloob Piracha (University of Kent, Department of Economics, 2002)
In this paper, using the framework of a Roy theoretical model, we examine the performance of return migrants in Albania. We ask two questions: (i) Had they chosen not to migrate, what would be the performance of return migrants compared to the non-migrants? and (ii) What would be the performance of non-migrants had they decided to migrate and return? Both the selection estimates and the semi-parametric approach allow us to conclude that the flows of return migrants are negatively selected. We find that, had they decided to migrate and come back, the non-migrants would have earned more than twice the wages of return migrants.
Keywords: F22; J61; 330; migration; self-selection; Albania; Rückwanderung; Albanien; Migranten